Water Recovery From Produced Water Via Forward Osmosis - Lim, Siow Yoke (Universiti Sains Malaysia, 2017)
Water recovery from synthetic produced water via forward osmosis was performed in this work using thin film composite membrane. The effect of oil concentration, draw solution concentration and draw solution cross flow velocity on membrane performance were studied. Three oil concentrations in feed solutions which are 10 ppm, 25 ppm and 50 ppm were used in this forward osmosis process. Whereas, the draw solution concentrations and draw solution cross flow velocities were manipulated to 1 M, 1.5 M, 2 M and 6 GPH, 8 GPH, 10 GPH respectively. Contact angle measurement showed that the thin film composite membrane is hydrophilic with contact angle less than 90° which is 60.3°. With the increased of oil concentration from 10 ppm to 50 ppm, the permeate flux had been reduced due to the increased of cake layer. On the other hand, the increment of draw solution concentration from 1 M NaCl to 2 M NaCl had enhanced the membrane performance with improved permeate flux as greater driving force in term of osmotic pressure difference was created to draw the water from the feed side. When the cross flow velocity increase from 6 GPH to 10 GPH, the permeate flux was also increased due to the increasing surface shear. The thin film composite membrane was found to have an average oil rejection of 99.76 % and flux of 1.06 L/m2.h.